Welfare assessment of goat kids subjected to a nutritional trial - de Oliveira, Daiana; Molina de Almeida Teixeira, Izabelle Auxiliadora; Figueiredo de Souza, Samuel; de Resende, Kleber Tomás (Revista Acadêmica Ciência Animal, 2018)
Many animals are subjected to experimental trials which impose some kind of physical and psychological suffering, and some of those methodologies are still used in nutritional experiments. Our purpose was to evaluate the welfare of suckling goat kids in a nutritional trial when submitted to feed restriction and housed in metabolic cages. Firstly a circadian rhythm trial was conducted to assess the behavior rhythm of goat kids under these conditions. Following this study, behavioral observations were conducted with the ongoing nutrition experiment. Direct observations with continuous recording were carried out with 27 Saanen goat kids (male, female and castrated males), submitted to three nutritional regimes (0%, 24.3% and 52.3% of feed restriction). Feed consumption was daily controlled and body weight was measured at birth and weekly until 5 weeks of age. All animals presented stereotypes, however female kids bit the bars more often (p = 0.04) and for longer time (p = 0.0094) than other animals. Goat kids under severe feed restriction presented reduced reaction to humans (p = 0.03), standing still for longer periods and presented signals of learned helplessness. This study showed that goat kids’ welfare was compromised during the nutritional experiment. New approaches within nutritional science research are highly encouraged, in order to keep the welfare integrity of animals used in research.